(untitled) (Research, Society and Development, 2021)
The scarcity and lack of drinking water are the most serious challenges of the 21st century. Several factors can compromise the water quality, highlighting the final destination of domestic sewage, and the inadequate disposal of solid urban and industrial waste. This work aims to carry out a literature review on pollutants and contaminants in water, as well as directing solar energy in different types of distillers (basin, pyramid, capillary film, mech and cascade) for potable water. Furthermore, discriminate the characteristics, differences and advantages existing between the main models of distillers. The methodology of this work was carried out in the main and most important national and international databases in the field of desalination and solar energy. Water intended for human consumption needs to be drinkable and in compliance with microbiological, physical-chemical and radioactive standards, in order not to pose health risks. Solar distillation consists of heating water by the sun’s rays, enabling the production of steam that is condensed on a cold surface and collected as water-product, producing pure water. Therefore, solar stills can be used for domestic purposes, especially in regions without access to electricity, as it is a social technology that has provided socioeconomic and environmental benefits, since it favors social dissemination, making possible its individual or collective use and providing decontaminated water through this sustainable and low-cost technology.